A study that aims to understand what type of brand stories promote engagement amongst Starbucks SA instagram followers using the brand positioning theory - Nsibande, Tintswalo (The IIE, 2017)
Storytelling has is one of the oldest forms of communication, with the growth of social media it has made it possible for marketers to communicate to the masses in the form of storytelling. The consumer has now become the prosumer who as is an active storyteller. Platforms such as Instagram can be used as a tool to position brands stories that engage the prosumer. The researcher wishes to evaluate the type of brand stories that encourage engagement with Starbucks SA followers on Instagram in context with the brand positioning theory. The research project was prompted due to the growth of video and how it has taken the media by storm. The study wishes to understand the phenomena of storytelling and how everyday people engage with the video stories that positioned on social media platforms such as Instagram. Qualitative content analysis using non-probable sampling to collect the data. Findings from the research presented key insights that people are more prone to engage with stories that are real because they are able to connect and relate, and a result the people engagement was quite high. The study aims to contribute to growing brand storytelling as a tool to position brands and engage with people on social media.
Keywords: Social Media; Digital Communication; Consumer Behaviour; Brands; Branding; Storytelling; Digital Storytelling